PENINGKATAN LAYANAN POSPAY DENGAN TEKNOLOGI BUSINESS PROCESS ANALYSIS (BPA) PADA PT. POS INDONESIA AREA KOTA MALANG - Rizqiyatul Khoiriyah (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2021)
PT. Pos Indonesia has a postal payment service (postpay) or System Online Payment Point (SOPP). Postpay services that are already running must be continuously improved so that they can develop properly. This makes it important to analyze the business processes that run on the postpay service at PT. Pos Indonesia Malang City Area so that later it can be known and identified opportunities for better business process improvement. The purpose of this study is to analyze the business processes that run on payment services (postpay) and identify opportunities to improve the payment service business process (postpay) at PT. Pos Indonesia Malang City. Based on the analysis of ongoing business processes, it was found that the payment service business process (postpay) of PT. Pos Indonesia in the Malang City area has been running according to existing procedures but has limitations on the queuing system, namely customers who will send goods and postpay payments still use a one-way queue. From these weaknesses and limitations, a business process with a two-lane queuing system was proposed, but it could also run flexibly with the previous one-line queuing system. The proposed two-lane queuing system, it can save time and increase the number of customers that can be served by PT. Pos Indonesia in Malang City area.